Expand of Alkhoms 30KV Power Distribution Network (The International Journal of Engineering & Information Technology (IJEIT), 2024)
One of the aims of the General ElectricalCompany of Libya (GECOL) is to supply the customerswith electric energy a wording to the standard specification.Alkhoms is a Libyan city and it is one of GECOL areas.Because of the conditions increasing of the loads in Alkhomsand in all Libyan cities, the electric network should be ableto feed the increasing and future loads. So it is necessary toadopt a strategic plan for future expanding of the network.The aim of this paper is to know the operating state of theelectrical power system by the conditions of the powercirculation, as well as developing the network until 2023 andstudying the proposed solutions to solve the problemsAlkhoms – Libya network. This paper has been usedNEPLAN software which had estimated and solved thefuture expanding problems of Alkhoms networks.